Utilization of cumulative antibiograms for public health surveillance: Trends in Escherichia coli and Klebsiella pneumoniae susceptibility, Massachusetts, 2008–2018. (27th February 2021) - Vo, Quynh T.; Klevens, R. Monina; Bolstorff, Barbara; Barton, Kerri; Cumming, Melissa; Blumenthal, Jennifer A.; Troppy, T. Scott; Gerth, Joseph M.; DeMaria, Alfred
Abstract: Background: Antimicrobial resistance is an urgent public health threat. Identifying trends in antimicrobial susceptibility can inform public health policy at the state and local levels. Objective: To determine the ability of statewide antibiogram aggregation for public health surveillance to identify changes in antimicrobial resistance trends. Design: Facility-level trend analysis. Methods: Crude and adjusted trend analyses of the susceptibility of Escherichia coli and Klebsiella pneumoniae to particular antibiotics, as reported by aggregated antibiograms, were examined from 2008 through 2018. Multivariable regression analyses via generalized linear mixed models were used to examine associations between hospital characteristics and trends of E. coli and K. pneumoniae susceptibility to ciprofloxacin and ceftriaxone. Results: E. coli and K. pneumoniae showed inverse trends in drug susceptibility over time. K. pneumoniae susceptibility to fluoroquinolones increased by 5% between 2008 and 2018 ( P < .05). In contrast, E. coli susceptibility declined during the same period to ceftriaxone (6%), gentamicin (4%), and fluoroquinolones (4%) ( P < .05). When compared to Boston hospitals, E. coli isolates from hospitals in other regions had a >4% higher proportion of susceptibility to ciprofloxacin and a >3% higher proportion of susceptibility to ceftriaxone ( P < .05). Isolates of K. pneumoniae had higher susceptibility to ciprofloxacin (>3%) and ceftriaxone (>1.5%) in all regions when compared to Boston hospitals ( P < .05). Conclusions: Cumulative antibiograms can be used to monitor antimicrobial resistance, to discern regional and facility differences, and to detect changes in trends. Furthermore, because the number of years that hospitals contributed reports to the state-level aggregate had no significant influence on susceptibility trends, other states should not be discouraged by incomplete hospital compliance.